The Co-construction of Knowledge and the Use of Critical Thinking in Academic Virtual Forums - Pulido González, Oscar Arnol (Universidad Santo Tomás, 2017)
This paper aims to report a research carried out with students of an advanced English course in a distant education undergraduate TEFL program at Universidad Santo Tomas. The main objective of the research was to determine patterns of co-construction of knowledge, and find evidences of the use of critical thinking in the virtual forums used in the English course. This was done through the application of two instruments: an adaptation of Gunawardena, Lowe & Anderson’s (1997) interaction analysis model, and an instrument that surveyed Paul’s universal intellectual standards (2007), which are standards that can be applied to thinking whenever one is interested in checking the quality of reasoning about a problem, issue or situation. The study followed a qualitative descriptive research design, and data was collected through a content analysis of the students’ written posts. The outcome of the study was the characterization of the students’ online interaction through the identification of phases of interaction and the evaluation of the quality of reasoning. The study also showed the need for teachers to propose virtual forum themes that promote critical thinking development in students.